Biografie polsko-żydowskie i żydowsko-polskie: rekonesans ponawiany - Czyżak, Agnieszka (Poznańskie Studia Polonistyczne. Seria Literacka, 2013)
The article contains reflections on changes in biographical writing, especially biography of persons of heterogenous ethnic identity. The biographies are not only reconstructions of an individual’s life, but also a clear testimony and reflection of changes in collective consciousness. It turns out that biographies also discover, in a peculiar way, the author’s identity, who, in the process of selection and creation of a biographical text, reveals a part of their own history. This aspect is clearly seen in texts by second and third generation Holocaust survivors, and is demonstrated by interpretations of Magdalena Tulli’s Włoskie szpilki [Italian High Heels] and Piotr Paziński’s Pensjonat [Boarding house].